DEVELOPING GALL MIDGE RESISTANT RICE (ORYZA SATIVA L.) HYBRIDS USING THREE LINE APPROACH - SAMEENA BEGUM, V. RAM REDDY; B. SRINIVAS; CH. ARUNA KUMARI (The Bioscan, 2019)
Six cytoplasmic male sterile lines (CMS) and seven testers of rice procured from Regional Agricultural Research Station (RARS), Polasa, Jagtial were crossed in Line × Tester mating design to develop heterotic rice hybrids resistant to gall midge. Among six CMS (Cytoplasmic Male Sterile) lines evaluated, the lines JMS 19A and JMS 20A had desired performance. The highest standard heterosis for grain yield and other yield attributes over the check varieties (US 312 and JGL 384) was recorded in the cross combination JMS 19A × JR 80 followed by JMS 19A × JBR 6 and JMS 19A × JR 83 involving these CMS lines. Further, these crosses exhibited moderate resistance to gall midge. Therefore, these aforesaid lines are promising genotypes in the future to develop successful three-line gall midge resistant rice hybrids for the Northern Telangana zone.